2005
DOI: 10.1097/01.psy.0000151745.67285.c2
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholesterol and Cognitive Performance in the Framingham Heart Study

Abstract: Lower naturally occurring TC levels are associated with poorer performance on cognitive measures, which place high demands on abstract reasoning, attention/concentration, word fluency, and executive functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
109
3
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(126 citation statements)
references
References 40 publications
12
109
3
2
Order By: Relevance
“…Prospective longitudinal studies also revealed that hypercholesterolaemia was associated with a protective effect for development of dementia and cognitive decline in the Australian elderly aged 75 years and over (15). Lower naturally occurring TC levels are associated with poorer performance on cognitive measures among elderly aged 55 to 88 years in the Framingham Heart Study (16). Further, in a 26 year follow-up study of elderly, serum cholesterol levels decreased in elderly who developed mild cognitive impairment, while increased in those who maintained normal cognition in Asian elderly (12).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Prospective longitudinal studies also revealed that hypercholesterolaemia was associated with a protective effect for development of dementia and cognitive decline in the Australian elderly aged 75 years and over (15). Lower naturally occurring TC levels are associated with poorer performance on cognitive measures among elderly aged 55 to 88 years in the Framingham Heart Study (16). Further, in a 26 year follow-up study of elderly, serum cholesterol levels decreased in elderly who developed mild cognitive impairment, while increased in those who maintained normal cognition in Asian elderly (12).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, previous research indicated that higher consumption of tea, which is linked to lower cholesterol level, was proved to take a protective effect on cognition (7), and higher cholesterol was linked to faster cognitive decline among patients with Alzheimer's disease (8). In contrast, other studies provide contradictory findings that demonstrated no association between cholesterol concentrations and cognitive impairment or dementia (9,10), and even that higher concentrations of cholesterol were associated with a decreased risk of cognitive impairment among the elderly (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, Zhang and collaborators [66] found that high cholesterol intake is strongly correlated with poor performance in cognitive tests on school children (6−16 years of age). Other studies demonstrated that greater intake of cholesterol and saturated fat increased the risk for impaired cognitive function in middle-aged or aged populations [18,33,42,58]. Although we are aware of the relative risks of high cholesterol intake, we still do not know the biological mechanisms behind its actions in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 93%
“…A standardized measure of effect (Cohen d) of lovastatin on endpoints adjusted for baseline values was calculated using the mITT population. Because cholesterol levels have been linked to cognitive performance, 20 we investigated an exploratory multivariable model, comparing fully evaluable treatment groups after treatment and adjusting for baseline cognitive performance and baseline total cholesterol. Reliable change index analysis was also conducted on primary outcomes.…”
mentioning
confidence: 99%